Down syndrome: perinatal mortality risks with each additional week of expectant management†. (14th March 2016) - Sparks, Teresa N.; Griffin, Emily; Page, Jessica; Pilliod, Rachel; Shaffer, Brian L.; Caughey, Aaron B.
Abstract: Objective: To evaluate the gestational age (GA) at which perinatal mortality risk is minimized for fetuses with Down syndrome (DS). Methods: Retrospective cohort of singleton pregnancies delivered between 24 and 41 weeks, using 2005–2006 United States linked birth and death certificate data. Among fetal DS cases, prospective risk of intrauterine fetal demise (IUFD) and risk of infant death were calculated for each week, and composite risk of fetal/infant mortality with expectant management was compared to delivery. Results: Of 3 113 098 pregnancies, 1766 had fetal DS (0.06%). IUFD occurred in 7.4% with DS, and infant death in 6.5%. Prospective risk of IUFD increased from 37 weeks onward to reach 50.7 per 1000 pregnancies (95% CI 33.2–68.3) at 42 weeks. Comparing mortality with expectant management to delivery, expectant management carried increasing risk from 38 (RR 1.18; 95% CI 1.05–1.33) to 41 weeks (RR 1.84; 95% CI 1.66–2.05). Further, number needed to deliver to avoid one excess death decreased from 38 (109.17; 95% CI 64.52–344.83) to 41 weeks (24.08; 95% CI 20.59–29.04). Conclusions: Although further research is needed to clarify risk factors for fetal and neonatal death in cases of DS, risk of perinatal mortality appears to be minimized with delivery at 38 weeks. © 2016 John Wiley & Sons, Ltd. Abstract : What's Already Known About This Topic? Pregnancies with Down syndrome have an increased risk of intrauterine fetal demise (IUFD), and mortality for infants with Down syndrome is higher than for those unaffected. What Does This Study Add? This study weighs the risk of expectant management against that with delivery at each gestational age (GA) for fetuses with Down syndrome. It addresses a gap in our current understanding of GA‐specific perinatal mortality risks, and considers optimal timing of delivery for pregnancies with fetal Down syndrome.